INVESTIGATING THE IMPACT OF RESISTANCE ECONOMY MANAGEMENTCOMPONENTS ON BANKING POLICYMAKING (CASE STUDY: SEPAH BANK) (CAHIERS MAGELLANES-NS, 2024)
The present study investigates the impact of resistance economy management components on banking policy in Sepah Bank. The present study is applied and field research. The statistical population of the present study included all 1800 employees of Sepah Bank branches in Tehran in 2022.  A convenience random method and Cochran's formula were used to determine the sample size, and 317 employees of Sepah Bank branches in Tehran were studied. A researcher-made questionnaire was used in this study to collect the desired data and information. Its validity was confirmed by experts and its reliability through Cronbach's alpha was obtained to be 0.81. The structural equation method and LISREL software were used to analyze the data. Testing the primary hypothesis and sub-hypotheses revealed a positive and significant relationship between all the components of resistance economy management and the three dimensions of Sepah Bank's organizational development. Therefore, the sub-hypotheses of the study are confirmed.